Pengaruh Kadar Nitrogen dalam Media pada Pembuatan Protease Menggunakan Bacillus megaterium DSM 319 - Trismilah Trismilah; Sumaryanto Sumaryanto (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
The media components and fermentation conditions play an important role for the result of fermentation processes, for instance nitrogen is one of the element which is influence for the growth of microorganism. Therefore it is needed the available media formulation for the optimal growth of microorganism with high productivity. It was shown in this protease production experiment by using Bacillus megaterium DSM 319 with media of Geolitti Cantoni (G&C) with modified of urea as source of nitrogen. The variation of carbon and nitrogen ratio which are used in this process are 3 : 0.8, 3: 1.5,3 :2,3: 2.5. Fermentation conditions were adjusted : temperature at 37°C, pH 7.5 and agitation of 250 rpm. The result of this process indicated that carbon and nitrogen ratio of 3 : 2 giving highest enzyme activity at 18 hours. The other results such are specific activity 6.552 Unit / protein mg, specific growth rate (u max/h) 0.074, duplication time (t jam) 9.367, coeffisient convert (Yx/s) 0.23.